Boundedness of Toeplitz Type Operators Associated to Fractional and Pseudo-Differential Operators on Orlicz Space (Journal of Partial Differential Equations, 2021)
In this paper, the boundedness from Lebesgue space to Orlicz space of certain Toeplitz type operator related to the fractional and pseudo-differential operatorsis obtained.
Keywords: Toeplitz type operator; pseudo-differential operator; BMO space; Orlicz space.